Construction of lean-to-roof at walkway / Muhammad Raihan Mohd Razlan - Mohd Razlan, Muhammad Raihan (Universiti Teknologi Mara, Perak, 2018)
Universiti Sains Islam Malaysia (USIM) is an emerging Islamic university which is fully owned and funded by the Malaysian Government. Being the 12th Public Institution of Higher learning, it aims to spearhead knowledge and be the global reference centre for Islamic Science. USIM adopts a balanced approach between the physical and spiritual aspects, not only in the academic programmes offered, but is also widely practised throughout the university including administration and management levels. Against this backdrop, USIM embraces a holistic approach towards the delivery of knowledge, which unites revelational sciences (Naqli knowledge) and the rational sciences (Aqli knowledge). USIM thus offers a unique model to Islamic Higher Education setting it apart from other Islamic universities worldwide. The integration of religious sciences together with the social and physical sciences in all its programmes provides a comprehensive understanding of current global problems and offers a fresh alternative in solving them.